2015
DOI: 10.1161/jaha.114.001218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Left Ventricular Hypertrophy on Troponin Release During Acute Myocardial Infarction: New Insights From a Comprehensive Translational Study

Abstract: BackgroundBiomarkers are frequently used to estimate infarct size (IS) as an endpoint in experimental and clinical studies. Here, we prospectively studied the impact of left ventricular (LV) hypertrophy (LVH) on biomarker release in clinical and experimental myocardial infarction (MI).Methods and ResultsST‐segment elevation myocardial infarction (STEMI) patients (n=140) were monitored for total creatine kinase (CK) and cardiac troponin I (cTnI) over 72 hours postinfarction and were examined by cardiac magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…CAD enhanced myocardial release of troponin, which, however, was documented also in patients without significant CAD. Moreover, according with previous reports, 26,27 it must be emphasized that in our study LVH markedly increased myocardial release of troponin induced by stress. In a recent study evaluating the impact of LVH on troponin release during myocardial infarction, it was estimated that the peak of hs-cTnI overestimates infarct size by approximately 30% in the presence of LVH.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…CAD enhanced myocardial release of troponin, which, however, was documented also in patients without significant CAD. Moreover, according with previous reports, 26,27 it must be emphasized that in our study LVH markedly increased myocardial release of troponin induced by stress. In a recent study evaluating the impact of LVH on troponin release during myocardial infarction, it was estimated that the peak of hs-cTnI overestimates infarct size by approximately 30% in the presence of LVH.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study evaluating the impact of LVH on troponin release during myocardial infarction, it was estimated that the peak of hs-cTnI overestimates infarct size by approximately 30% in the presence of LVH. 26 However, even more critical is the issue of small increments of troponin in patients with chest pain and LVH, given the high prevalence (20–25%) of LVH in the general population 26 and the possibility of false-positive diagnoses of myocardial infarction in this setting. In addition, small increments in circulating troponin I 27 and T 28 have been reported, in patients with LVH, even in the absence of chest pain and any other acute pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple logistic regression analysis showed, however, that the concentrations of CK-MB, cTnI, NT-proBNP and CRP were not independent predictors of LVR. Although acute-phase cTnI and CRP concentrations have been reported to predict LVR [25], cTnI release during STEMI was reported to be poorly predictive of post-MI LV dysfunction [26]. In contrast, serial measurements of B-type natriuretic peptide, cTnI, and CRP were found to be predictive of LVR after acute MI [27].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports showed that the hypertrophied myocardium exhibits an accelerated loss of high-energy phosphate content and a greater accumulation of tissue lactate and hydrogen ions during ischemia as well as an accelerated calcium overload during early reperfusion [19,20]. It should be noted that the infarct size in patients with LV hypertrophy may be significantly overestimated when based on the determination of cardiac enzymes such as the peak and AUC plasma values of cardiac troponin I [21]. In the present study, the results were expressed based on the weight of the myocardial tissue, thus avoiding this source of potential error.…”
Section: Discussionmentioning
confidence: 99%